Milk Powder Formulation Based on Durian Seed Flour, Cocoa, Wild Honey “Tikung” and Creamer - Ester Apriani UT; Yohana S.K. Dewi; Tri Rahayuni (FoodTech: Jurnal Teknologi Pangan, 2022)
Durian seed flour has nutritional value as a food but until now extract of durian seed only to make a powder.  The nutritional content of durian seeds has the potential as an ingredient for making milk especially milk powder so that it can be stored for a long time. The purpose of this study was to obtain a durian seed flour formulation that produces the best physicochemical and organoleptic characteristics of milk powder. The method used was a randomized block design with one factor consisting with 4 formulations. The formulation of milk powder that it made of durian seed flour, cocoa powder, vegetable creamer, honey, carboxymethyl cellulose, lecithin and water showed the best chemical and sensory characteristics. The milk powder has a water content of 6.59%; total soluble solids 10.50 °Brix; ash content 3.26%; protein content 7.73%; fat content 25,742%.  The sensory characteristics of milk powder have acolor 4.17 (prefer); taste 3.23 (like); fragrance 3.73 (like); and overall likes 3.60 (likes).